Mercenaries and Security Contractors in the 21st Century : The Past and Future of Private Force - Cusumano, Eugenio; Kinsey, Christopher; Parr, Robert (Routledge, 2025)
This book examines the debate over private security contractors, using historical and contemporary cases, including several non-Western examples.Since the end of the Cold War, security privatization has grown in its geographical outreach, breadth, and scope. This pervasive expansion of the private military and security market warrants a systematic investigation of commercial actors' involvement in the variety of tasks associated with the provision of violence, ranging from combat to vessel protection and cybersecurity. Combining theoretical and empirical approaches, the essays in this volume provide a historical investigation into private force that extends beyond Europe and the United States.By focusing on recent developments, such as the extensive involvement of Russian mercenaries in Ukraine, new evidence from the Global South, and the added historical depth given to the study of commercial providers of warfare, this volume questions the endurance of norms like the mercenary taboo and the state monopoly of violence. In doing so, it sheds new light on the past, present, and future of private security.This book will be of much interest to students of private security studies, military studies, security studies, and international relations.
Keywords: Private security services.; mercenaries; private security contractors; private force; proxy warfare; Global South; elektronické knihy; electronic books